Pemberdayaan UMKM Sebagai Strategi Meningkatkan Daya Saing di Era Globalisasi - Rasidi, Moh.; Bambang; Yoga Pratama, M.; Noer Hidayat, Moh.; Rahman, Taufiqur (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Furniture business assistance in Alas Kandang Besuk Village aims to increase the competitiveness of local Micro, Small and Medium Enterprises (MSMEs) through various strategies and approaches. This mentoring program includes technical training in making furniture products, business management, digital marketing, and financial management. Apart from that, business networks were also strengthened between local furniture entrepreneurs and the wider market, both at regional and national levels The results of this assistance show an increase in furniture product quality, operational efficiency and better marketing capabilities among MSME players. In addition, there has been a significant increase in income and absorption of local labor. This assistance has also succeeded in encouraging product innovation and business diversification, which has contributed to increasing the competitiveness of furniture MSMEs in Alas Kandang Besuk Village.